Inhibition of BET Protein Function Suppressed the Overactivation of the Canonical NF-κB Signaling Pathway in 6-OHDA-Lesioned Rat Model of Levodopa-Induced Dyskinesia - Wan, Ying; Han, Li; Rong, Lu; Yang, Shuyuan; Song, Lu; Wu, Na; Liu, Zhenguo; Gan, Jing (Frontiers in Neuroscience, 2022)
Background Neuroinflammation is involved in the mechanisms of levodopa-induced dyskinesia (LID). The canonical NF-κB activation signaling pathway plays a critical role in the neuroinflammation development and BET protein-induced NF-κB-mediated neuroinflammation. The inhibition of the BET protein function has been reported to alleviate LID; however, its association with the canonical NF-κB signaling pathway in the 6-OHDA-lesioned striatum of the LID rat model remains unknown. Accordingly, we identified the status of the canonical NF-κB signaling pathway in the 6-OHDA-lesioned striatum of the LID rat model and whether the anti-dyskinetic effect of the BET inhibitor JQ1 was associated with its suppression on NF-κB-mediated neuroinflammation. Methods 6-OHDA PD rat models were treated with either L-dopa plus JQ1 or L-dopa alone. L-dopa treatment was given for 2 weeks, and the JQ1 treatment was given for 3 weeks and was initiated a week prior to L-dopa treatment. As a control, the sham rats were treated with JQ1 or Veh for 3 weeks. The ALO AIM assessment and cylinder test were performed during the treatment. Glial activation markers, pro-inflammatory substances, and critical proteins in the canonical NF-κB signaling pathway were tested in the lesioned striatum after the final treatment. Results JQ1 effectively alleviated LID without influencing motor improvement. In the lesioned striatum, L-dopa triggered an overactivation of the canonical NF-κB signaling pathway, with an increase in the phospho-IKKα/β, phospho-IκBα, and NF-κB nuclear translocation and its phosphorylation at Ser 536 and Ser 276 sites (p < 0.01 vs. sham group). L-dopa induced an overexpression of the pro-inflammatory substances of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and inducible nitric oxide synthase (iNOS), and the glial activation markers CD68 and GFAP. All the molecular changes were greatly inhibited by JQ1. Conclusion L-dopa triggered an overactivation of the canonical NF-κB signaling pathway, leading to an enhanced neuroinflammation response in the 6-OHDA-lesioned striatum of LID rat models. The inhibition of the BET protein function significantly suppressed the activation of the canonical NF-κB signaling pathway in the striatum, alleviating the neuroinflammation response and the severity of LID.